2011
DOI: 10.1038/nm.2446
|View full text |Cite
|
Sign up to set email alerts
|

A human memory T cell subset with stem cell–like properties

Abstract: Immunological memory is thought to depend upon a stem cell-like, self-renewing population of lymphocytes capable of differentiating into effector cells in response to antigen re-exposure. Here we describe a long-lived human memory T-cell population that displays enhanced self-renewal and multipotent capacity to derive central memory, effector memory and effector T cells. These cells, specific for multiple viral and self-tumor antigens, were found within a CD45RO−, CCR7+, CD45RA+, CD62L+, CD27+, CD28+ and IL-7R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

104
2,033
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 1,614 publications
(2,147 citation statements)
references
References 58 publications
104
2,033
2
8
Order By: Relevance
“…Improved clinical efficacy of adoptive T cell therapy could be reached by generating tumor-specific T cell products with an early differentiation state, as they show superior longevity and proliferative capacity. 1-3,5-9,15-21,24,25,29-35 This could be accomplished by inhibition of the AKT pathway, as was previously shown by us and others. 15-21 In this study, we aimed to further optimize AKT-inhibited CD8 + T cells by exploring AKT-inhibitors with diverse modality of action, and further characterize these cells for their phenotype, transcriptome, metabolism and functionality.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Improved clinical efficacy of adoptive T cell therapy could be reached by generating tumor-specific T cell products with an early differentiation state, as they show superior longevity and proliferative capacity. 1-3,5-9,15-21,24,25,29-35 This could be accomplished by inhibition of the AKT pathway, as was previously shown by us and others. 15-21 In this study, we aimed to further optimize AKT-inhibited CD8 + T cells by exploring AKT-inhibitors with diverse modality of action, and further characterize these cells for their phenotype, transcriptome, metabolism and functionality.…”
Section: Discussionmentioning
confidence: 61%
“…To determine whether both allosteric and ATP-competitive AKT-inhibitors show similarities with any of the natural T cell subsets, a principal component analysis was performed. This was based on a set of 900 transcripts which are differentially expressed in the T cell subsets T N , T SCM , T CM and effector memory T cells (T EM ) as previously described by Gattinoni et al 24 This analysis revealed that despite their unique transcriptome profiles, both allosteric AKT-inhibitors (left panel) as well as ATP-competitive AKT-inhibitors (right panel) resembled the naturally occurring T SCM subset (Figure 3B). In contrast, DMSO-treated control T cells clustered more closely with the natural occurring T EM cells.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations